2013
DOI: 10.1007/s11064-013-1031-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of In Vivo Antioxidant Ability in the Brain of Rats Fed Tannin

Abstract: The effect of the oral administration of mimosa tannin (MMT) on the rat intra-hippocampal antioxidant ability was examined. Wistar rats at the age of 6 weeks were reared for 8 weeks with the rodent diet (RD) consisting of 0.1 g/kg of MMT (RD-MMT). The antioxidant ability of rat brain was evaluated from the decay of a brain-blood-barrier permeable stable nitroxide, 3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine-1-oxyl (PCAM) measured by the microdialysis-electron spin resonance system under a freely moving st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…An ex vivo study run on the nematode Caenorhabditis elegans showed that pomegranate puniclalgan-derived urolithins exhibited a protective effect against amyloid β1-42–induced neurotoxicity and paralysis [ 138 ]. An in vivo study indicated that rapid decline in the nitroxide, 3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine-1-oxyl (PCAM), may be attributed to higher brain antioxidant ability in mice fed a diet containing mimosa tannin (MMT), compared to other mice fed a normal rodent diet [ 139 ]. Further research is needed to assess the effects of metabolites obtained from other flavan-3-ol sources, such as grape, and to explore the bioavailability in humans, compared to that in rats [ 140 ].…”
Section: Biological Effects Of Gut-biotransformed Metabolites Of Tanninsmentioning
confidence: 99%
“…An ex vivo study run on the nematode Caenorhabditis elegans showed that pomegranate puniclalgan-derived urolithins exhibited a protective effect against amyloid β1-42–induced neurotoxicity and paralysis [ 138 ]. An in vivo study indicated that rapid decline in the nitroxide, 3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine-1-oxyl (PCAM), may be attributed to higher brain antioxidant ability in mice fed a diet containing mimosa tannin (MMT), compared to other mice fed a normal rodent diet [ 139 ]. Further research is needed to assess the effects of metabolites obtained from other flavan-3-ol sources, such as grape, and to explore the bioavailability in humans, compared to that in rats [ 140 ].…”
Section: Biological Effects Of Gut-biotransformed Metabolites Of Tanninsmentioning
confidence: 99%
“…Finally, the prospects to target the prevention and/or the onset of neurodegenerative disorders through ENC administration might also occur in vivo, as several studies demonstrated that oral administration of tannins produces brain CNS benefits [Nakajima et al, ; Farbood et al, ]. In addition, over the last decade, development of the so‐called drug carriers such as liposomes‐ and nanoparticle‐mediated drug delivery could represents one promising strategy to successfully increase the CNS penetration of several therapeutic moieties, included nutraceuticals and natural compounds [Sahni et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, different tannins provide neuroprotection owing to their antioxidant-and anti-inflammatory activity [Rojanathammanee et al, 2013], the ability to inhibit b-secretase [Youn and Jun, 2013] as well as anomalous tau protein aggregation [Yao et al, 2013] and to restore gastrointestinal function in several inflammatory conditions [Rosillo et al, 2012]. Furthermore, several orally administered tannins and tannins-rich extracts have been shown to provide benefits at CNS level [Nakajima et al, 2013].…”
mentioning
confidence: 99%